The taming of PARP1 and its impact on NAD+ metabolism - Sarah Hurtado-Bagès; Gunnar Knobloch; Andreas G. Ladurner; Marcus Buschbeck (Elsevier, 2020)
Background: Poly-ADP-ribose polymerases (PARPs) are key mediators of cellular stress response. They are intimately linked to cellular metabolism through the consumption of NAD+. PARP1/ARTD1 in the nucleus is the major NAD+ consuming activity and plays a key role in maintaining genomic integrity. Scope of review: In this review, we discuss how different organelles are linked through NAD+ metabolism and how PARP1 activation in the nucleus can impact the function of distant organelles. We discuss how differentiated cells tame PARP1 function by upregulating an endogenous inhibitor, the histone variant macroH2A1.1. Major conclusions: The presence of macroH2A1.1, particularly in differentiated cells, raises the threshold for the activation of PARP1 with consequences for DNA repair, gene transcription, and NAD+ homeostasis.